ANALISIS TERHADAP KEBIJAKAN PENGAMPUNAN PAJAK DALAM INVESTASI Di INDONESIA - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2021)
tax amnesty (tax amnesty) will be able to increase investment as expected by the government in an effort to increase economic growth, especially at this time the tax ratio shows a low number as evidence that there are still many taxpayers who do not / have not exercised their rights & obligations in accordance with laws and regulations. -invitation. The problem in this research is how the government policy in providing tax amnesty in investment in Indonesia. This study uses a normative juridical approach and an empirical approach. Data collection techniques are carried out by literature study and field studies. The data are then analyzed and discussed qualitatively. Based on the research results, regulatory inaccuracy, both in substance and in the form of legislation, will weaken the principle of legality, tax amnesty does not automatically increase state revenue, likewise tax amnesty does not automatically increase investment. Tax amnesty as an incentive needs policy support from other sectors so as to create the expected investment climate. Vertical and horizontal justice in tax imposition is insufficient when applied to tax amnesty. In tax amnesty, justice that brings benefits to society and the state should be emphasized.